Dekonstruksi Tindak Tutur Ilokusi Direktif dalam â€œOne Piece Film: Redâ€ - Nurjannah, Sitti; Usman, Usman; Agussalim, Andi (Nuances of Indonesian Language, 2025)
This research is a qualitative research with a descriptive method which aims to describe the deconstruction of directive illocutionary speech acts contained in One Piece Film: Red. Data was collected through proficient free-involved listening techniques and data transcription. The data source comes from the dialogue of the characters in One Piece Film: Red. The research results show that the deconstruction of directive illocutionary speech acts contained in One Piece Film: Red reveals the ambiguity and instability of meaning in each utterance. Commands given by certain characters often have multiple meanings, depending on the context of the conversation and the relationships between the characters. It is hoped that this research can contribute to the study of pragmatic linguistics, especially in understanding the nature of meaning instability in speech acts through popular media such as films. Keywords: Deconstruction, Directive Speech Act, One Piece Film: Red.